Effects of treated biomass wood fly ash as a partial substitute for fly ash in a geopolymer mortar system. (2nd May 2023) - Ates, Fatmanur; Park, Kyu Tae; Kim, Kyeong Woo; Woo, Byeong-Hun; Kim, Hong Gi
Highlights: Biomass wood fly ash was treated through calcination and ball milling process. The chemical composition and particle size distribution changed due to treatment. The inclusion of biomass wood fly ash to binder improved the strength properties. Better porosity and strength performance is achieved by the treatment of biomass wood fly ash. Abstract: The use of biomass for energy production is becoming increasingly common. However, one of the significant problems when using biomass is the ash produced in the incineration process. Existing studies have shown the possibility of using residual biomass ashes in cement-treated materials, but its low properties have reduced compressive and flexural strength. Accordingly, some treatment methods research has also been done to enhance the properties of biomass waste materials for incorporation into the concrete matrix. On the other hand, there is a growing interest in replacing conventional ordinary Portland cement with geopolymer composite as the binder matrix in concrete due to increasing global environmental issues like greenhouse gas emissions. Therefore, this study investigates the effect of the treatment process on the physical and mechanical performance of geopolymer mortar incorporating Biomass Wood Fly Ash (BWFA) and Fly Ash (FA) for industrial applications. BWFA was treated through calcination and ball milling techniques. Both non-treated and treated BWFA were used to replace FA at different replacement ratios: 0 %, 10 %, 30 %, and 50 % by total binder weight. Test specimens were evaluated regarding porosity, compressive strength, flexural strength, X-ray diffraction analysis, thermogravimetric analysis, and microstructure development at ages 1, 3, and 7 days. The outcomes demonstrated considerable improvements in treated mortars' physical and mechanical characteristics. The inclusion of treated BWFA enhanced compressive and flexural strength. Besides, the Control mix and treated BWFA specimens performed better porosity while non-treated BWFA specimens showed better thermogravimetric performance.